A conceptual paper on the performance measure usage according to BSC perspective within the Malaysian electrical & elactronics sector / Amri Mohamad and Yuserrie Zainuddin - Mohamad, Amri; Zainuddin, Yuserrie (2015)
The objective of this study is to investigate on the performance measure usage within the Malaysian E&E manufacturing firms’ performance. Basically the theoretical gaps are concentrated on the issue of focusing solely on the financial measurements to measure the firm’s performance. And it has been discussed at length in the literature about the insufficiency of relying on the financial indicators only as the sole indicator to gauge firms performance. The main aim of this paper is to investigate on the performance measure usage according to BSC perspectives within the E&E manufacturers that will serve as a basis for future research with regards to this issue within the E&E manufacturing performance in Malaysia.